Respuesta :
Answer:
Step-by-step explanation:
Suppose J, K, L, M, N are points on the same line.
MK = MN + (-KN) = MN - KN = 9x - 11 - x - 3 = 8x - 14
Since LK = MK and LK = 7x - 10, then
7x - 10 = 8x - 14
8x - 7x = -10 + 14
x = 4
LJ = MK + KJ
MK = LK = 7x - 10 = 7(4) - 10 = 28 - 10 = 18
LJ = 18 + 28 = 46
Read more on Brainly.com - https://brainly.com/question/5067118#readmore
Answer:
LJ=46
Step-by-step explanation:
Suppose J,K,L,M,N are all point lie on the same line
We are given tha LM=MK
LK=7x-10
KN=x+3
MN=9x-11
KJ=28
We have to find LJ
MK=MN+NK=MN+(-KN)=MN-KN
MK=[tex]9k-11-x-3[/tex]
MK=[tex]8x-14[/tex]
LK=MK=8x-14
[tex]7x-10=8x-14[/tex]
[tex]14-10=8x-7x[/tex]
[tex]x=4[/tex]
[tex]LJ=LK+KJ[/tex]
Substitute x=4
LJ=[tex]7(4)-10+28=46[/tex]
Hence, LJ=46